MARIA SÍMBOLO DE DEUS E DA MULHER: estudo das Imagens de Maria na Teologia da Libertação - Santos, Léia Rosa dos (2006)
Mary s figure is going through an emancipation process; from a divine and pure Mary to a concrete, woman and human Mary. Her emancipation is a result of the achievements and victories that women today have sought and pursued. It is evident that these changes have occurred exclusively in one determined theological trend, that using a liberating hermeneutic and the feminine as it is shown to us today, thinks Mary as a concrete figure (woman). However, as a religious symbol, she will always be a Virgin, a Mother and a Wife, and new interpretations will always be an attempt to overcome the model of an ideal woman projected in Mary s symbolism seen through the lens of a patriarchal structure. Parallel to this new interpretation of the religious symbolism of Mary, is found the structure of the feminine as the new hermeneutic key to think about God, a perspective that reveals the divine transcendence and the humanity present in a woman s figure as well. God-Mother is a very well used term in popular circles, from a biblical reading of the Old Testament texts and is also restrict to the academy, meaning that will hardly be used in an evangelical religious realm and in society, for the culture is still impregnated with patriarchal structures where man s supremacy hinders the feminine thought as a structure that transcends its human nature.